Gambaran Kasus Gondongan pada Siswa SD Normal Islam Samarinda - Wardani, Nunuk Kusuma; Saputri, Deby Indah; Nugraha, Purwa; Nozomi, Alwan Zakki; Noor, Muhammad; Wisnuwardani, Ratih Wirapuspita; Pakki, Irfansyah Baharuddin (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: Mumps is a contagious disease caused by paramyxovirus infection that primarily affects children and adolescents. In 2024, a surge of mumps cases was reported in Samarinda, particularly at Sekolah Dasar Normal Islam Samarinda. This study aimed to describe the characteristics of mumps cases based on age, sex, and epidemiological distribution at the school during October–November 2024.Methods: This descriptive observational study utilized primary and secondary data. Purposive sampling was applied to include students who met the clinical diagnostic criteria for mumps, identified through school health reports and direct observation. Data collection covered number of cases, age, sex, symptoms, and transmission patterns. Analysis was performed descriptively using Microsoft Excel. A total of 78 students were identified with mumps symptoms. The index case was reported on October 3, 2024, in a male fifth-grade student presenting parotid gland swelling, fever, and history of close contact within the past 25 days.Results: The majority of cases occurred among male students (61.5%), particularly those in grades 5 and 6, with 11 years old being the most affected group. The most common clinical manifestations included fever and parotid gland swelling. Notably, none of the students had received the MMR vaccination. The epidemic curve showed a sharp increase in October 2024, followed by a decline in November, with an overall attack rate of 12.5%.Conclusion: Low immunization coverage, overcrowded classrooms, and delays in early detection played a significant role in facilitating transmission within the school. Strengthening vaccination programs, implementing health education, improving hygiene protocols, and ensuring early isolation of suspected cases are recommended to control and prevent further mumps outbreaks in school settings. Keywords: Mumps; epidemiology; imunization; disease prevention; school children